Gaze behaviour during the soccer penalty kick: An investigation of the effects of strategy and anxiety - Noel, B.; van der Kamp, J. (International Journal of Sport Psychology, 2012)
Gaze behaviour of penalty takers who either adopted a goalkeeper independent or goalkeeper dependent strategy was compared for low and high anxiety conditions. Results showed clear performance advantages for the goalkeeper independent strategy as compared to the goalkeeper dependent strategy. Balls were shot further away from the goalkeeper and less saves were made. The superior performance of the goalkeeper independent strategy was associated with longer times spent viewing to the target area inside the goal and toward the ball, and shorter looking times at the goalkeeper. The moderate, but significant increase in anxiety, however, did not affect gaze behaviour and performance. The present experiment is the first to demonstrate that the benefits of the goalkeeper independent strategy, relative to the goalkeeper dependent strategy, result from more optimal gaze patterns.